ANALISIS PENGARUH BUDAYA ORGANISASI DAN PENGENDALIAN INTERN TERHADAP KINERJA SEKTOR PUBLIK DENGAN AKUNTABILITAS SEBAGAI VARIABEL MODERASI (Studi Kasus Pada Dinas Perindustrian dan Tenaga Kerja Kabupaten Bojonegoro) - Ardilla, Heppy Kurnia (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2018)
The importance of performance report is needed to evaluate how far the institution or organization are able to implement their vision and mission. One of its consistency is the need of performance support activities by improving the organizational culture, internal control, and accountability. This research objective is to obtain the empirical evidences about the influence of organizational culture and internal control toward public sector performance with the accountability as moderation variable.This research is categorized as quantitative research using primary data taken from questioners. The research population is the employees in the Office of Industry and Manpower of Bojonegoro Regency. The sampling technique used in this research is purposive sampling. The samplesobtained consist of 36 respondents. The date is analyzed using multiple linear regression analysis and processed using the help of SPSS software version 16.0.The result of this research shows that (1)Partially, organizational culture influences positively and significantly toward the public sector performance, (2) Partially, internal control influences positively and significantly toward the public sector performance, (3) Partially, accountability influences positively and significantly toward the public sector performance, (4) simultaneously, organizational culture, internal control and accountability influences positively and significantly toward the public sector performance, (5) Accountability moderates positively and significantly the influence of organizational culture toward the public sector performance, and (6) Accountability moderates positively and significantly the influence of internal control toward the public sector performance.